Validated Stability Indicating HPTLC Method for the Determination of Dutasteride in Pharmaceutical Dosage Forms. (21st July 2011) - Patel, Dipti B.; Patel, Natubhai J.; Patel, Sejal K.; Patel, Paresh U.
Abstract : This paper describes simple, sensitive, precise, specific, and stability-indicating high-performance thin-layer chromatographic method for the determination of dutasteride (DUTA) in bulk and tablet formulation. Validation was carried out in compliance with International Conference on Harmonization guidelines. The thin-layer chromatographic method employed aluminium plates precoated with silica gel G60F254 as stationary phase. The solvent system consisted of toluene/methanol/triethylamine (9 : 2 : 1, v/v/v). This solvent system was found to give compact spots for dutasteride withR f value 0.71 ± 0.01. Densitometric analysis of DUTA was carried out in the absorbance mode at 274 nm. Linear regression analysis showed good linearity (r 2 = 0.9989 ) with respect to peak area in the concentration range of 200–3000 ng per spot. The method was validated for precision, accuracy, specificity, and robustness. Pure drug was subjected to acid and alkali hydrolysis, oxidation, photo degradation, dry heat and wet heat treatment. The drug underwent degradation under acidic, basic, oxidative, and wet heat conditions. The degraded products were well separated from the pure drug. Statistical analysis proved that the method is reproducible and selective for estimation of DUTA in bulk and tablets. As the method could effectively separate the drugs from their degradation products, it can be employed as a stability indicating method.